W obronie interesów gospodarczych państwa. Procesy przed sądami bydgoskimi w latach 1946-1956 (Kronika Bydgoska, 2014)
The judicial system after the war functioned based on the prewar regulations. For the communist authorities, however, law had become - to a large extent - a tool to achieve their own political goals. Special legal acts, in the form of decrees, were issued. New, “quasi-judicial” bodies were established, which partially had taken over functions of judicial authorities. Legal regulations were freely interpreted, at one’s own discretion. Article 22 of the Decree on Particularly Serious Crimes during rebuilding of the State of June 13, 1946 was a model example of legal regulations, which the authority was “stretching” to their needs. Extensive interpretation made that many social behaviors were classified as crimes under this article. Human behaviors showed the attitude of the nation to the then situation in the country and knowledge on events in Poland and the world.